The Role of English Day Strategy in Enhancing Speaking Skills: A Case Study in Darul Falah Boarding School - Suseno, Ranna Parahita Wukirsari Dewi; Rosdiana, Aliva (Universitas Muhammadiyah Barru, 2025)
This study aims to examine how the English Day strategy in English learning contributes to the improvement of students’ speaking skills. Fluency in English has become more than an ability in an increasingly globalized world. This study used a qualitative case study design supported by a mixed-methods approach, applying interviews with English teachers, student questionnaires, and pre-post speaking assessments analysis from 20 students of Darul Falah Boarding School Klaten. The results show that English Day greatly improves students' confidence and speaking fluency, however, through limited practice, students writing skills remained underdeveloped, indicating an imbalance in the integration of language skills. These findings highlight the value of immersive teaching methods backed by thorough resources and engaged teachers.